KARAT DAUN ( Hemilieia vastatrix ) PADA TANAMAN KOPI ARABIKA DI PERKEBUNAN RAKYAT LAMAKNEN SELATAN - Fadillah, Resti; Pitaloka, Maria D. A.; Humoen, Maria Imelda; Banamtuan, Elesta; Leo, Maria Y. M. K.; Andiewati, Suci; Rohi, Jullyo Gideon (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2025)
South Lamaknen District is the center of coffee production in Belu Regency. Coffee production is influenced by external and internal factors, H. vastatrix attacks are among the main external factors that limit coffee production in this district. Data information related to leaf rust disease in Belu district does not yet exist. Data on the distribution and severity of coffee leaf rust disease in this district do not yet exist. Such data is needed to determine appropriate control strategies to improve coffee production. The study aimed to obtain data on the severity of coffee leaf rust disease in smallholder coffee plantations in Belu Regency. The research method used was purposive random sampling (PRS) in the Belu people's coffee center in Lakmaras and Henes Villages, South Lamaknen District, with a geographical location between 9 ْ0.9' 26.61